Penelitian Bahasa dengan Analisis Framing - Suharyo Suharyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
This paper offers a framing analysis approach as one of the alternatives that can be tried to reveal linguistic symptoms, especially discourse in the mass media. Framing analysis does not only see language in terms of its structure, but also from other dimensions.To be able to apply the framing analysis in the discourse study, knowledge and understanding of the theory and essential factors of framing analysis is needed. the function of mass media and the theory of hegemony. In addition, also need to know the characteristics of framing analysis, such as (1) facts, reality is actually the result of social construction, (2) mass media is a social construction agent in defining reality, (3) news is not a reflection of reality (language relativeity) , (4) news is not an objective fact, (5) journalists are actually not news reporters, but construction agents who have alignments, and (6) readers have their own interpretations of the news presented. The aspects that need to be considered are the schmatic, script, thematic, and rhetorical aspects and writing strategies.